Design of miniaturized Planar Inverted-F Antenna (PIFA) for LTE700M / Muhammad Feroze Akbar Jalaludin Khan - Akbar Jalaludin Khan, Muhammad Feroze (2019)
In 2008, FCC has auctioned 700 MHz band for commercialize and public safety usage. The 700 MHz has been boosting to mobile services such as for long term evolution (LTE) application. The benefits of 700 MHz band for LTE application are lower path loss, higher coverage range and lower design cost. However, the challenges of this band are larger antenna design and its complexity to achieve higher bandwidth. PIF A is a potential candidate to support 700 MHz band as it is known for its low profile, low cost and easy built in for portable devices. Yet, the major challenges for PIF A are its larger size for lower operating band and its narrow bandwidth nature. In this research, miniaturized PIF A will be designed for lower band application; LTE700M. The major challenges of PIF A for L TE700M are narrow bandwidth and larger antenna design. This study presents the impact of step stairs and slotted ground techniques for bandwidth enhancement and miniaturization process. The main radiators of PIFA have been branched into several radiating arms which. provide optimized dimensions. Then, stair-shaped geometry has been added near main radiator which enhanced bandwidth for both lower band and higher band. Finally, the size of the finite ground is gradually reduced and optimized using slotted ground in order to achieve optimum size reductions.